PENINGKATAN KUALITAS IBU DAN ANAK MELALUI PENCEGAHAN STUNTING DI DESA RIDOGALIH - Lestari, Siti Ayu; Oktafiani RNK, Afiifah; Aprilina, Vita; Al Ramadhan, Muhammad Fakhran (An-Nizam, 2024)
Community service activities carried out by students at the Islamic University 45 Bekasi aim to overcome the high rate of stunting in Ridogalih Village, Cibarusah District, Bekasi Regency. This initiative began with direct observations of the health and nutritional conditions of the community, including inspections of health facilities and child rearing patterns. The student team also conducted in-depth interviews with mothers and local health workers to gain information regarding knowledge and practices related to stunting. After collecting data, the team developed and implemented educational sessions that focused on increasing awareness about balanced nutrition, breastfeeding techniques, and reproductive health practices. The methods used include presentations, demonstrations and interactive discussions to ensure the material is easy for participants to understand and apply. The results of this activity show significant progress in several aspects. The increase in participants' knowledge regarding stunting prevention is reflected in a better understanding of nutrition and health. In addition, there have been real changes in the implementation of health practices, such as improvements in diet and breastfeeding techniques. The effectiveness of the program can also be seen from reports that participants are starting to apply the prevention strategies that have been taught. Although long-term results will take time to fully emerge, early indications are that stunting rates in the village are starting to decline. With a data-based approach and active community participation, this activity succeeded in having a positive impact in handling stunting in Ridogalih Village.